2022
DOI: 10.1002/cam4.5194
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the regulatory T cells signature and relevant Foxp3/STAT3 axis in esophageal cancer

Abstract: Background: Regulatory T cells (Tregs) have an important role in accelerating the immunosuppression of tumor. Tregs regulation is a hopeful strategy to improve the dismal prognosis of Esophageal cancer (EC), while its mechanisms have not yet been fully clarified. Methods: To characterize the role of Tregs in EC, we comprehensively explored its prognostic value, clinical pathology partnership, related biological functions and potential mechanisms at transcriptome level. Through the integrated analysis of GEO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“… 30 , 31 Increased infiltration of immune cells, irrespective of the biomarker, displayed a trend toward an improved prognosis. As earlier reports suggest, higher density of PD-1, 32 FOXP3, 33 CD3, 34 CD4, 27 and CD8 25 positive immune cell infiltration exhibited improved efficacy against PD-1 blockade (Supplementary Fig. S8C-L).…”
Section: Exploratory Analysissupporting
confidence: 77%
“… 30 , 31 Increased infiltration of immune cells, irrespective of the biomarker, displayed a trend toward an improved prognosis. As earlier reports suggest, higher density of PD-1, 32 FOXP3, 33 CD3, 34 CD4, 27 and CD8 25 positive immune cell infiltration exhibited improved efficacy against PD-1 blockade (Supplementary Fig. S8C-L).…”
Section: Exploratory Analysissupporting
confidence: 77%
“…This helps to upregulate Foxp3 expression in ESCC. By increasing Foxp3 expression through STAT3 modification of Foxp3+Treg transcription process, activating the STAT3/Foxp3 signaling pathway within ESCC tissue hinders macrophage phagocytosis and increases Foxp3+Treg immunosuppressive activity, which helps ESCC evade the body’s immune response ( 26 ). Furthermore, upon recognition of its receptor ST2, IL-33 attracts a significant number of Foxp3+Tregs to congregate in the stroma of ESCC, thereby initiating the IL-33/ST2/Foxp3+Treg/COX-2/PGs regulatory pathway, encouraging Foxp3+Treg secretion of cyclooxygenase-2 (COX-2) and enabling the conversion and production of prostaglandins (PGs).…”
Section: Mechanisms Of Foxp3 and Foxp3+ Treg Cell Pro-cancer In Malig...mentioning
confidence: 99%
“…The tumour microenvironment (TME) has a significant impact on tumour development, owing to its ability to suppress the immune system by inhibiting and depleting T, B, and natural killer cells. This action weakens the defense system of the body against tumours, enabling them to evade the immune system [ [4] , [5] , [6] , [7] ]. Numerous studies have demonstrated an association between multiple resistant cell populations in the TME and development, invasion, and metastasis [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%